Keratin synthesis in normal mouse epithelia and in squamous cell carcinomas: evidence in tumors for masked mRNA species coding for high molecular weight keratin polypeptides. - Winter, H (1983)
Transplantable mouse squamous cell carcinomas (SCC), originally derived either from back skin or forestomach epithelium, do not synthesize high molecular weight keratin polypeptides [greater than 60 kilodaltons (kDa)] involved in the process of terminal differentiation in the corresponding normal tissues. The in vivo tumor keratin spectra consist of only low molecular weight keratin subunits at 60, 58, 52, 50, 47, and 46 kDa, each encoded by its own mRNA and encountered also in normal epidermis and forestomach epithelium. In addition, both tumors express a mRNA-dependent 40-kDa protein, whereas a 56-kDa protein and its mRNA are selectively found only in the forestomach tumor. Translation of mRNAs from both tumors in a cell-free system does not only generate analogues of the in vivo tumor keratin polypeptides, but also both SCC possess an additional mRNA coding in vitro for a 67-kDa keratin subunit that is not expressed, however, in the carcinomas in vivo. The identity of this in vitro synthesized keratin member with a 67-kDa keratin polypeptide of both normal epidermis and forestomach epithelium was confirmed by comparison of charge properties and peptide mapping. With regard to this particular keratin polypeptide, the tumors are obviously able to sequester the polypeptide's mRNA in an untranslatable state in the cells.